Cardiovascular pharmacology of K2P17.1 (TASK-4, TALK-2) two-pore-domain K+ channels - Staudacher, Ingo; Illg, Claudius; Chai, Sam; Deschenes, Isabelle; Seehausen, Sebastian; Gramlich, Dominik; Müller, Mara Elena; Wieder, Teresa; Rahm, Ann-Kathrin; Mayer, Christina; Schweizer, Patrick Alexander; Katus, Hugo; et al. (Naunyn-Schmiedeberg's archives of pharmacology, 2018)
K2P17.1 (TASK-4, TALK-2) potassium channels are expressed in the heart and represent potential targets for pharmacological management of atrial and ventricular arrhythmias. Reduced K2P17.1 expression was found in atria and ventricles of heart failure (HF) patients. Modulation of K2P17.1 currents by antiarrhythmic compounds has not been comprehensively studied to date. The objective of this study was to investigate acute effects of clinically relevant antiarrhythmic drugs on human K2P17.1 channels to provide a more complete picture of K2P17.1 electropharmacology. Whole-cell patch clamp and two-electrode voltage clamp electrophysiology was employed to study human K2P17.1 channel pharmacology. K2P17.1 channels expressed in Xenopus laevis oocytes were screened for sensitivity to antiarrhythmic drugs, revealing significant activation by propafenone (+ 296%; 100 μM), quinidine (+ 58%; 100 μM), mexiletine (+ 21%; 100 μM), propranolol (+ 139%; 100 μM), and metoprolol (+ 17%; 100 μM) within 60 min. In addition, the currents were inhibited by amiodarone (− 13%; 100 μM), sotalol (− 10%; 100 μM), verapamil (− 21%; 100 μM), and ranolazine (− 8%; 100 μM). K2P17.1 channels were not significantly affected by ajmaline and carvedilol. Concentration-dependent K2P17.1 activation by propafenone was characterized in more detail. The onset of activation was fast, and current-voltage relationships were not modulated by propafenone. K2P17.1 activation was confirmed in mammalian Chinese hamster ovary cells, revealing 7.8-fold current increase by 100 μM propafenone. Human K2P17.1 channels were sensitive to multiple antiarrhythmic drugs. Differential pharmacological regulation of repolarizing K2P17.1 background K+ channels may be employed for personalized antiarrhythmic therapy.
Gesehen am 21.04.2020
Im Titel ist "2P" in K2P13.1 tiefgestellt
Im Titel ist "+" in K+ hochgestellt